Analysis of the prospects of the application of the electroplastic effect in the processes of processing metals with pressure - D. V. Minko (Литьë и металлургия)
The mechanical properties of metals change temporarily or permanently under the influence of a high density electric current in the deformation zone. This phenomenon is called electroplasticity, and its use makes it possible to intensify the process of pressure treatment of electrically conductive materials, including those that are difficult to machine using existing technologies. By now, there is no established point of view on the physical nature of the manifestation of electroplasticity, although this effect itself has already found practical application. The electrical plasticity of metals and their alloys was studied under various loading conditions, including tensile, compression, and bending tests. The article analyzes the theoretical mechanisms of the occurrence of electroplasticity described in scientific publications, the results of studies of the electroplastic properties of various metals or metal alloys, and recommendations for the practical application of the electroplastic effect.